Implementation of Good Faith Principles in Trade Contracts in Indonesia - Alpian Mega Nugraha; Fathan Dhony Fadil; Talitha Khumairoh; Diky Dikrurahman; Deni Yusup Permana (International Journal Labs, 2024)
The principle of good faith is a fundamental basis for establishing contractual relationships, including trade contracts in Indonesia. The application of this principle is important to create a conducive, fair and transparent business climate. The purpose of this study is to examine the application of the principle of good faith in trade contracts in Indonesia. This research uses qualitative research methods by collecting data using literature review techniques. then after the data is collected, it is analyzed using steps such as selecting data, presenting data and finally making conclusions. The research findings show that the implementation of the principle of good faith in trade contracts in Indonesia is regulated in Article 1338 paragraph (3) of the Civil Code, which emphasizes the importance of the principle of good faith and fair dealing in the entire contract process, starting from negotiation, contract arrangement, contract implementation, to dissolution. contract. In Indonesian law, good faith is applied not only during contract implementation but also in the pre-contract stage, namely before the contract is signed. This is important to protect the parties involved in the transaction from losses. The use of the good faith principle in commercial contracts in Indonesia has also been applied in several judicial cases, such as in life insurance contracts, where the court ensured that the good faith principle was applied to protect the rights of the parties involved. Apart from that, the principle of good faith is also applied in the choice of law for foreign direct investment contracts Indonesia.